Revisión de la literatura de las técnicas y métodos de medición del Capital Intelectual - Otero Ibañez, Elizabeth Raquel (2018)
The current investigation reviews the state of the art of the techniques and methods of measurement of Intellectual Capital existing up to 2015, examining the linked literature to establish a classification based on the strengths and limitations found. The method used consists of three stages, the first one concentrates on a collection of sources documented in the databases Ebsco, ProQuest and ScienceDirect, to then select those that use quantitative techniques in the measurement and finally an analysis and classification of linked literature. A total of 68 investigations have been reviewed, of which 17 belong to the state of the art, finding an evolutionary trend in the measurement techniques of indicators. The study concludes that Intellectual Capital is a subject in permanent intellectual discussion and highlights the existence of remaining deficiencies such as the inclusion of ontological aspects in the calculation of current indicators.